Implementasi JConnect Mobile Dalam Meningkatan Pelayanan Nasabah: Studi Bank Jatim Syariah Kediri - Pratiwi, Maheswary Sekar; Mala, Iva Khoiril; Romadhon, Bagus; Sutantri, Sutantri (Universitas Islam Tribakti Lirboyo Kediri, 2024)
With the advancement of technology in the 5.0 and modern era, effective and efficient communication continues to develop, hence the creation of the internet. The Internet is used by people and organizations to conduct business. For banking, one form of service implemented in the digital era is mobile banking. Bank Jatim Syari'ah launched the latest product in the digitalization era, namely JConnect Mobile with its various features. This study aims to determine the role of JConnect mobile in improving services to customers of Bank Jatim Syari'ah, this research uses qualitative research with library research methods and direct field studies, so not only from theory but going directly to the field to research. Jconnect mobile service quality through the dimensions of security, speed and accuracy has an important role in improving services to customers using JConnect mobile products.